Perfil epidemiológico de sífilis congênita no Hospital Universitário de Santa Maria de 2010 a 2014 - Argemi, Carla Tourem (2016)
The objective of this study is to identify and describe the cases reported / investigated of Congenital Syphilis in the Santa Maria’s University Hospital (HUSM), Rio Grande do Sul, Brazil, in the period of 2010 to 2014. Is a retrospective, cross-sectional, study in which secondary data found in records of notification/investigation of Congenital Syphilis Information System notification where evaluated. 128 records notification/investigation Congenital Syphilis where evaluated. The survey instrument was developed based on research of Congenital Syphilis records and pregnant women, where with the data collected has built up a database, which was submitted to descriptive statistical analysis. The analyzed variables consisted on the genitor: sociodemographic; realization or not of the prenatal care; period of maternal diagnosis of the Syphilis, nontreponemal test achievement in prenatal and childbirth; Prenatal treponemic test and delivery; treatment performed in pregnancy, partner treatment. The variables relating to infant were: not treponemal test, cerebrospinal fluid change, not treponemic test cerebrospinal fluid; radiological diagnosis; clinical diagnosis; in child treatment regimen; developments. Results: 128 cases of congenital syphilis were reported during the study. Pregnant women analyzed were the age from 20 to 35 years old, all of them of white color, educational level of 5th to 8th grade incomplete, underwent the prenatal care, had the diagnosis carried out in the third-trimestrer or childbirth, with inadequate treatment and with partners who were not treated. Newborns were male, white, have been notified within seven days after the birth date, treponemal test in peripheral blood reagent and asymptomatic in most cases. Three cases with non treponemal test in the reagent liquor six cerebrospinal change and a case with abnormal X-ray of the long bones, and more than half of the cases received treatment with Penicillin Cristalina for 10 days. Conclusion: Persisting vertical transmission, there is failure in the health care network focused on prenatal quality.